POTENSI PEMANFAATAN LIMBAH PADAT KELAPA SAWIT SEBAGAI UPAYA MENINGKATKAN EFISIENSI ENERGI DI PABRIK KELAPA SAWIT - Gusri, Lailal; Putri, Prameswari Amalia; Manab, Abdul; Rabiula, Andre (Program Studi Teknik Lingkungan, Fakultas Teknik, Universitas Mahasaraswati Denpasar, Bali, 2025)
The palm oil industry has a significant impact on the regional and national economy, generating employment, especially for farmers. Crude palm oil (CPO) can be processed into edible oil, cosmetics, and biofuels, making it a strategic commodity in global trade. However, this industry also produces abundant solid and liquid waste, such as shells, fibers, and empty fruit bunches. Factory waste must be managed and processed to prevent environmental pollution. Poor waste management can lead to various environmental problems, necessitating effective and sustainable management strategies. This type of solid waste has the potential to be used as an alternative energy source and raw material for value-added products. The objective was to determine the utilization of palm oil solid waste and its percentage, as an effort to optimize industrial waste management. The methods used included direct observation of the processing and utilization of solid waste at the factory, collection of production data, and a review of relevant literature. The results showed that empty fruit bunches are used as compost and mulch in plantations, shells are used as boiler fuel to generate steam energy, and fiber is used as supplementary fuel. According to the literature review, this solid waste still has potential for further development, such as the production of briquettes, pellets, and biomass-based activated carbon. Optimizing the utilization of palm oil solid waste can increase the energy efficiency of factories and reduce the volume of waste.